Perendoscopic Placement of Palliative Stent for Obstructive Jaundice Caused by Head of Pancreas Malignancy in Dr Moewardi General Hospital-Surakarta - Aritantri Darmayani; Triyanta Yuli Pramana; Paulus Kusnanto (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Pancreatic cancer is difficult to diagnose in early stage. Malignant bile duct obstruction is a severe complication of pancreatic cancer, which can lead to poor outcomes including cholangitis, delayed treatment, reduced quality of life, and increased mortality. Perendoscopic placement of stents is a method widely used in the management of various malignant and benign pancreatico-biliary abnormalities. A 70-year-old woman came to Dr Moewardi General Hospital in Surakarta with the chief complaint of yellowish skin and eyes since one month before hospital admission. Patient was diagnosed with obstructive jaundice due to suspected of advanced stage pancreatic cancer. Subsequently, patient underwent endoscopic retrograde cholangiopancreatography (ERCP) which revealed an intrahepatic and extrahepatic bile ducts dilatation due to pancreatic tumor which infiltrated common bile duct, thus self expandable metallic stent (SEMS) placement was performed. Furthermore, patients received palliative therapy due to inadequate chemotherapy requirement.